SYNTHESIS AND STRUCTURAL PROPERTIES OF Fe DOPED La0,8Sr0,2Ga0,8Mg0,2O3-d (LSGM) AS SOLID ELECTROLYTE FOR SOLID OXIDE FUEL CELL - (NIM 205 05 004), Rusmiati
ABSTRACT: Fuel cell is expected to be an alternative energy source to replace the fossil fuel. There are several benefits of using fuel cell as an energy source since fuel cell exhibits high efficiency, produce water and less pollutant substances at the end of process and uses renewable energy source such as hydrogen. Fuel cell is an electrochemical cell, which consists of two electrodes where reduction and oxidation process occur and the electrolyte placed between electrodes that acts as ionic conductor. Fuel cell are classified according to the type of electrolyte. One of the fuel cell type is the solid oxide fuel cell (SOFC), which consists of solid oxide material as electrolyte. For the SOFC application, oxide materials used as electrolyte must have high ionic conductivity in order to make oxygen ion move efficiently from cathode to anode to complete redox reaction and then producing electrical energy. Lanthanum Galate is an oxide material with perovskite structure and high ionic conductivity at high temperature and it have been used as an electrolyte for SOFC. Doping of Sr ion at La site and Mg ion at Ga site with La1-xSrxGa1-yMgyO3-d (LSGM) composition have increased ionic conductivity due to crystal defect introduced by doping. At present, LSGM are used for electrolyte material since it exhibits high ion oxygen conductivity. In order to reduce the fuel cell operational temperature, high ionic conductivity of electrolyte must be obtained at lower temperature. High ionic conductivity can be achieved by introducing impurity or defect into material. Doping with Fe for Mg site is expected to increase oxygen ion conductivity in LSGM, since Fe has higher valence number (+3) compared with Mg (+2). In this work, the LSGM and LSGMF (La0,8Sr0,2Ga0,8Mg0,2-xFexO3-d with x=0, 0.05, 0.1, 0.15) perovskite structure were synthesized by solid state reaction technique at various temperature, and it was sintered at highest operable temperature of the equipment that available in laboratory, that is 1450 oC for 12 hours. Crystal structures were analyzed using X-rays diffractometer and refined using Rietica Program. The cell parameters were determined with Le Bail refinement in cubic structure with space group Pm3m. The lattice parameter for La0,8Sr0,2Ga0,8Mg0,2-xFexO3-d with x = 0 (LSGM); x = 0.05 (LSGMF 1); x = 0.1 (LSGMF 2); x=0.15 (LSGMF 3) were a = 3.92023(1) A for LSGM, a = 3.9183(7) A for LSGMF 1, a = 3.9126(1) A for LSGMF 2, and a = 3.9061(3) A for LSGMF 3. Scanning Electron Microscope (SEM) and Energy Dispersive X-Ray Spectroscopy (EDX) is used to study the grain morphology and elements composition of the LSGM and LSGMF in order to analyze the effect of Fe substitution. The SEM image show that surface of the compound made into pellet form with pressure of 10N/cm2, consist of grains with porous. The LSGM and LSGMF grains diameter were about 0,5 up to 2 mm. Meanwhile, based on EDX data, doping Fe at Mg site shows Mg concentration decreasing, which is consistent with the initial composition. However, the increasing of Fe concentration was found to be smaller than the initial composition. The ionic conductivity as a function of temperature was measured using impedance analyzer with Electrochemical Impedance Spectroscopy (EIS) software. For higher Fe concentration, ionic conductivity is increasing with temperature between 150 oC-350 oC while at low Fe concentration ionic conductivity was constant.